In vitro antioxidant and antiproliferative activities of three Malaysian sea cucumber species - Althunibat, Osama Yousef; Hashim, Ridzwan; Bakhtiar, M. Taher; Mohd. Daud, Jamaludin; Ikeda, Masa-Aki; Ibrahim, Zali (EuroJournals Publishing, Inc., 2009)
The antioxidant and antiproliferative activities of aqueous and organic extracts from three sea cucumber species Holothuria scabra, Holothuria leucospilota and Stichopus chloronotus were studied. The result showed that aqueous extract of H. leucospilota contains the highest level of total phenols (9.7 mg GAE/g), while the lowest level was obtained from organic extract of H. scabra (1.53 mg GAE/g). An aqueous extract of S. chloronotus was the most efficient extract in scavenging of DPPH free radical, giving IC50 = 2.13 mg/ml. The aqueous extracts (50mg/ml) of H. scabra, H. leucospilota and S. chloronotus exhibited high antioxidant activities (77.46%, 64.03% and 80.58%, respectively) against linoleic acid free radical. Only an aqueous extract of S. chloronotus inhibited growth of C33A (human cervical cancer) and A549 (human non-small lung carcinoma) cancer cells, giving IC50 equal to 10.0 µg/ml and 28.0 µg/ml, respectively. On the other hand, the dose dependent antiproliferative effects of all organic extracts studied were observed on C33A and A549 cancer cells. This study, therefore, revealed that all the three species of Malaysian sea cucumber are potential sources of natural antioxidant and anticancer agents.